Is restraint a 'necessary evil' in mental health care? Mental health inpatients' and staff members' experience of physical restraint. (27th September 2017) - Wilson, Ceri; Rouse, Lorna; Rae, Sarah; Kar Ray, Manaan
Abstract: Restraint in mental health care has negative consequences, and guidelines/policies calling for its reduction have emerged internationally. However, there is tension between reducing restraint and maintaining safety. In order to reduce restraint, it is important to gain an understanding of the experience for all involved. The aim of the present study was to improve understanding of the experience of restraint for patients and staff with direct experience and witnesses. Interviews were conducted with 13 patients and 22 staff members from one UK National Health Service trust. The overarching theme, 'is restraint a necessary evil?', contained subthemes fitting into two ideas represented in the quote: 'it never is very nice but…it's a necessary evil'. It 'never is very nice' was demonstrated by the predominantly negative emotional and relational outcomes reported (distress, fear, dehumanizing, negative impact on staff/patient relationships, decreased job satisfaction). However, a common theme from both staff and patients was that, while restraint is 'never very nice', it is a 'necessary evil' when used as a last resort due to safety concerns. Mental health‐care providers are under political pressure from national governments to reduce restraint, which is important in terms of reducing its negative outcomes for patients and staff; however, more research is needed into alternatives to restraint, while addressing the safety concerns of all parties. We need to ensure that by reducing or eliminating restraint, mental health wards neither become, nor feel, unsafe to patients or staff.